The Obscure Becomes Vivid: perspectives on the (re)mediation of fairy lore by folklorists, performers and audiences. Issue 6 (February 2021) - Hield, Fay; Larrington, Carolyne; Hadley, Steven; Price, Sarah M.
No abstract available